Farmer producers meet innovators to advance the digital transformation of agriculture in Maharashtra - CGIAR (CGIAR Initiative on Digital Innovation, 2023)
Digital technologies can provide huge benefits to farmer organizations in countries such as India, for example by making tasks more efficient, access to market information or to new buyers and sellers. For this reason, there has been strong governmental support to create for conditions for digitalization to occur.